Getting Eyes in the Home: Child Protective Services Investigations and State Surveillance of Family Life - Fong, Kelley (American Sociological Review, 2020)
Each year, U.S. child protection authorities investigate millions of families, disproportionately poor families and families of color. These investigations involve multiple home visits to collect information across numerous personal domains. How does the state gain such widespread entrée into the intimate, domestic lives of marginalized families? Predominant theories of surveillance offer little insight into this process and its implications. Analyzing observations of child maltreatment investigations in Connecticut and interviews with professionals reporting maltreatment, state investigators, and investigated mothers, this article argues that coupling assistance with coercive authority—a hallmark of contemporary poverty governance—generates an expansive surveillance of U.S. families by attracting referrals from adjacent systems. Educational, medical, and other professionals invite investigations of families far beyond those ultimately deemed maltreating, with the hope that child protection authorities’ dual therapeutic and coercive capacities can rehabilitate families, especially marginalized families. Yet even when investigations close, this arrangement, in which service systems channel families to an entity with coercive power, fosters apprehension among families and thwarts their institutional engagement. These findings demonstrate how, in an era of welfare retrenchment, rehabilitative poverty governance renders marginalized populations hyper-visible to the state in ways that may reinforce inequality and marginality.